Taṭwīr Māddah Mahārah al-Qirāʾah min Khilāl Tarjamat al-Ḥikāyāt al-Shaʿbiyyah al-Indūnīsiyyah ilā al-Lughah al-ʿArabiyyah li Ṭalabat al-Madāris al-Thānawiyyah al-Islāmiyyah bi Indūnīsiyā - Effendy, Tisf Wanda (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2026)
The development of high-quality instructional materials is an essential aspect of effective language teaching, as the quality of teaching is closely related to the quality of the learning materials employed. This study aims to develop reading skill materials by translating Indonesian folktales into Arabic for students of Islamic senior secondary schools in Indonesia. The research adopts a modified Research and Development (R&D) model proposed by Borg and Gall (1989), consisting of six stages: (1) needs analysis, (2) product design, (3) expert validation, (4) product revision, (5) field testing, and (6) final product development. The study resulted in three major outcomes. First, it produced a set of reading materials based on translated Indonesian folktales, comprising a dedication page, preface, table of contents, reading texts, illustrated exercises, learner profile page, and references. Second, expert evaluations indicated that the developed materials were of excellent quality and suitable for use as supplementary resources in Arabic language instruction for Islamic senior secondary school students in Indonesia. Third, the study developed a user guide for both teachers and students to facilitate classroom implementation and support independent learning.